The effectiveness of the ethno-STEM-based Project-Based Learning (PjBL) model in enhancing critical thinking skills - Santi, Diana; Siswanto; Dewantaric, Nuryunita (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study aims to examine the effectiveness of the Project-Based Learning model with an Ethno-STEM approach in enhancing students’ critical thinking skills. This research employed a quantitative method using a quasi-experimental nonequivalent control group design, with sample selection conducted through purposive sampling. The sample was selected using purposive sampling. The research subjects were eighth-grade students, assigned to an experimental class and a control class. Data were collected through critical thinking skill tests in the form of essay questions administered before and after the treatment. The results of the independent sample t-test (0.001 < 0.05) indicate a significant difference in students’ critical thinking skills between the experimental and control groups. The N-Gain analysis shows that the increase in critical thinking skills in the experimental class (0.50) was higher than in the control class (0.34). Based on these findings, it can be concluded that the Project-Based Learning model with an Ethno-STEM approach is effective in improving students' critical thinking skills.